EPIDEMIOLOGICAL PROFILE OF PATIENTS WITH NON-VARICEAL UPPER GASTROINTESTINAL BLEEDING SECONDARY TO PEPTIC DISEASE IN A TERTIARY REFERRAL BRAZILIAN HOSPITAL - FORGERINI,Marcela (2021)
ABSTRACT BACKGROUND: Non-variceal upper gastrointestinal bleeding (NVUGIB) secondary to peptic ulcer disease is a medical digestive emergency and could be one of the most serious adverse drug reactions. OBJECTIVE: To identify the frequency of diagnosis of NVUGIB secondary to peptic ulcer disease. METHODS: Prospective and epidemiological study conducted in a tertiary referral Brazilian hospital, from July 2016 to December 2019. Upper gastrointestinal endoscopies (UGE) reports were evaluated daily. The diagnosis of NVUGIB secondary to peptic ulcer disease was defined through endoscopic findings of peptic ulcer and erosive gastric lesions, and clinical symptoms. The frequency of diagnosis of NVUGIB secondary to peptic ulcer disease was estimated through the ratio between the number of patients diagnosed and the number of patients underwent UGE in the same period. RESULTS: A total of 2,779 endoscopic reports (2,503 patients) were evaluated, and 178 patients were eligible. The total frequency of diagnosis of NVUGIB secondary to peptic ulcer disease was 7.1%. The annual frequency of diagnosis between 2017 and 2019 ranged from 9.3% to 5.7%. Most patients were men (72.8%); self-declared white (71.8%); older people (56.7%); and, had no familiar or personal history of gastrointestinal diseases (60.1%). 90% of the patients had a peptic ulcer and melena (62.8%). Patients made chronic use of low-dose aspirin (29.3%), other antiplatelet agents (21.9%) and, oral anticoagulants (11.2%); and non-steroidal anti-inflammatories use in the week a prior to the onset of clinical symptoms (25.8%). CONCLUSION: Seven in every 100 patients admitted and underwent UGE in a tertiary hospital were diagnosed with NVUGIB secondary to peptic ulcer disease.